Originally Posted by

**TheEmptySet** Since you didn't give the previous result we can only GUESS at what you need?

Here is my guess first note that

$\displaystyle \displaystyle \tan\left( \tan^{-1}(x)\right)=x$

Now if we take the derivative using the chain rule on the left hand side we get

$\displaystyle \displaystyle \frac{d}{dx}\tan\left( \tan^{-1}(x)\right)=\frac{d}{dx}x$

$\displaystyle \displaystyle \sec^2\left( \tan^{-1}(x)\right)\left(\frac{d}{dx} \tan^{-1}(x)\right)=1$

Now solving for the derivative we want gives

$\displaystyle \displaystyle \frac{d}{dx}\tan^{-1}(x)=\frac{1}{\sec^2(\tan^{-1}(x))}=...$

Now just use what you found out in this part of the problem.